Silence of the altars: researching sexual abuse in religious institutions in Catalonia (Spain) - Balcells, Marc (Fieldwork experiences in criminology and security studies, 2023)
Our research assessed clergymen’s perceptions of child sexual abuse in Catalonia (Spain) and identified elements pointing toward anomie and a discourse linked to the neutralization of the perpetrators’ criminal responsibility. The study included 20 interviews with diocesan priests and members of religious congregations: they highlighted the impact of sexual abuse on clergy, the plurality of sensitivities, the existence of discourses tending to idealization, the presence of neutralization techniques, and the existence of institutionalized and persistent anomie within the Catholic Church. To achieve these results, however, a lack of institutional cooperation complicated and limited data collection. The present chapter deals with the challenges experienced to reach the sources; how the sensitive nature of the topic had an impact on both interviewees and interviewers; and offers some insights into the research process as well as some recommendations.